Stereospecific synthesis of phosphatidylglycerol using a cyanoethyl phosphoramidite precursor. (September 2020) - Struzik, Zachary J.; Weerts, Ashley N.; Storch, Judith; Thompson, David H.
Graphical abstract: Highlights: A synthetic route to provide control over the PG stereocenters from solketal precursors. Approach potentially enables control over acyl chain identity. Acyl chain migration avoided by careful control over reaction time and conditions. Phosphoglycerol headgroup introduced using phosphoramidite intermediate. Abstract: Phosphatidylglycerols (PG) are a family of naturally occurring phospholipids that are responsible for critical operations within cells. PG are characterized by an ( R ) configuration in the diacyl glycerol backbone and an ( S ) configuration in the phosphoglycerol head group. Herein, we report a synthetic route to provide control over the PG stereocenters as well as control of the acyl chain identity.